Argumen Kontra Muhammad Imarah Atas Konsep Susunan al-Qur’an Ala Abid al-Jabiri - Desri Ari Enghariano (Institut Agama Islam Negeri Padangsidimpuan, 2021)
In an scientific context, thera are pros and cons in an issue that is normal. This reality also occurs in the study of the Qur’an. Among the modernist figures who propose a method in studying the Qur’an is Abed al-Jabri. He offered the idea of reconstructing the arrangement of the Qur’an. According to him, the arrangement of the Qur’an in the osman manuscirpts must be reviewed. This idea was refuted by Muhammad Imarah. He wrote a book, specifically to demolish Abed al-Jabri’s heretical ideas.The book is entitled “Radd Iftiraat al-Jabiri ‘Ala al-Qur’an al-Karim”.Therefore, this research aims to describe the Muhammad Imarah’s arguments againts the concept of Abed al-Jabri. The discussion includes the description of the figures of Abed al-Jabri and Muhammad Imarah, the secretaries of the Prophet Mohmmed, history of compiling the Qur’an, Muhammad Imarah’s rebuttal to the concept arrangement the Qur’an in the style of Abed al-Jabri. The method used in this research is analysis method. The results of this research is to explain that Abed al-Jabri and Muhammad Imarah are modern figures. Al-Jabri from Marocco and Muhammad Imarah from Egypt. Prophet Mohammed had many secretaries and they are divided in to groups. The format of the arrangement of the Qur’an is based on the instructions of the Prophet Mohammed. Al-Jabri’s arguments that became the basis of the idea of reconstruction the arrangement of verses and surah; 1) the Qur’an is very open for reformulation of the arrangement of verses and surahs. 2) The purpose of the idea of reconstructing the arrangement of the Qur’an is so that objectivity can be maintained. 3) All verses of the Qur’an have a sabab nuzul. Muhammad Imarah’s rebuttal; 1) Why switch from the divine God’s tartib, the arrangement that has existed since Lauh al-Mahfuzh and Gabriel taught the Prophet. 2) Qur’an is not a history book. 3) Al-Jabri’s claim is has no solid basis, because he was completely unable to name the salaf scholars who argued that all verses had a sabab nuzul.